Reference pricing with elastic demand for pharmaceuticals - Gonçalves, Ricardo (2016)
In this paper, we re‐examine the properties of two commonly adopted government reimbursement schemes for pharmaceuticals: reference pricing and fixed percentage reimbursement. We depart from the previous literature by assuming that the individual demand is price‐sensitive and depends on the copayment rate (i.e., the part paid by each consumer). We obtain two novel results under reference pricing: first, as the copayment rate increases, so do pharmaceutical prices; second, this increase in pharmaceutical prices reduces social welfare. Whilst reference pricing does emerge as a preferable reimbursement scheme, demand elasticities and the copayment rate interact in complex ways. This leads (unexpectedly) to the possibility that a higher copayment rate (lower reimbursement rate) results in higher government expenditure.